2015 IEEE First International Conference on DC Microgrids (ICDCM) 2015
DOI: 10.1109/icdcm.2015.7152025
|View full text |Cite
|
Sign up to set email alerts
|

Voltage weak DC microgrid

Abstract: This paper describes the behavior of voltage weak dc microgrids. These are dc microgrids with a relatively small system capacitance. The large amounts of stored energy in the passive component of a network has a considerable effect on the size of the fault currents, control and reliability. The use of a complex control approach to stabilize voltage weak microgrids is a possibility that requires further attention. In this paper, however, a simple way to stabilize such a system is proposed by limiting the rate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…With respect to inductance, the results of this paper are congruent with previous works [26,37], where a decrease in inductance leads to increased stability. Furthermore, from the equations in the previous section, it can be observed that the impedance (slope) of the droop controlled source has an upper and lower bound.…”
Section: Sensitivity Analysissupporting
confidence: 91%
See 2 more Smart Citations
“…With respect to inductance, the results of this paper are congruent with previous works [26,37], where a decrease in inductance leads to increased stability. Furthermore, from the equations in the previous section, it can be observed that the impedance (slope) of the droop controlled source has an upper and lower bound.…”
Section: Sensitivity Analysissupporting
confidence: 91%
“…P l is the load's power, U l is the voltage at which the load is linearized, and Z l is the (negative) impedance of the load [26].…”
Section: Loadsmentioning
confidence: 99%
See 1 more Smart Citation
“…The low inertia of DC distribution grids results in strict requirements on the control system [30]. It should be noted that low inertia grids are also a problem for future AC grids.…”
Section: Controlmentioning
confidence: 99%
“…With low system capacitance the short circuit currents can be significantly reduced, however control of these voltage weak systems is more challenging [22]. Protection selectivity in meshed grids is an important topic especially for fast protection strategies.…”
Section: A Over Current and Short Circuit Protectionmentioning
confidence: 99%